Pediculus capitis infestation according to sex and social factors in Argentina Infestação por Pediculus capitis segundo sexo e fatores sociais na Argentina - Silvia Catalá; Luis Junco; Rita Vaporaky (Universidade de São Paulo, 2005)
OBJECTIVE: To determine the intensity of Pediculus capitis infestation (abundance) among Argentinean schoolchildren. Children's sex and social stratum were analyzed as modifiers of the general prevalence and degree of parasitism. METHODS: The study included 1,370 schoolchildren (692 girls, 678 boys) from 26 schools of the province of La Rioja (21 public schools, five private schools). Classic prevalence was obtained as the percentage of children with nits and/or lice. Moreover, five degrees of parasitism were classified: 0) children with no signs of pediculosis; 0+) children with evidence of past infestation; 1) children with a recent infestation and low probability of active parasitism; 2) children with a recent infestation and high probability of active parasitism; 3) children with mobile lice (active pediculosis). RESULTS: The general prevalence was 61.4% (girls: 79%; boys: 44%, p<0.001). Private schools showed lower prevalence than public schools (p=0.02), especially due to the low prevalence in boys. Fifty percent of children were classified in classes 0 and 0+, 22% in class 1; and 28% in grades 2 and 3. The proportion of children in grade 3 was higher in public schools than in private schools. There were significant sexual differences in the intensity of parasitism for grades 2 and 3, where girls' rates exceeded twice those of boys'. CONCLUSIONS: Sex and social stratum are important modifiers of P. capitis general prevalence and degree of infestation. The classification of children by intensity of infestation allowed a more precise delimitation of this condition, which is especially important for disease surveillance and application of control measures. OBJETIVO: Determinar a intensidade de infestação (abundância) de Pediculus capitis em crianças argentinas em idade escolar. Analisar se sexo e classe social das crianças são fatores influentes na prevalência e grau de parasitismo. MÉTODOS: Foram examinados 1.370 alunos (692 meninas e 678 meninos), de 26 escolas (21 públicas e cinco particulares) da província de La Rioja, Argentina. A prevalência foi obtida pela percentagem de crianças com lêndeas e/ou piolhos. O parasitismo foi classificado em cinco graus: 0) crianças sem sinal de pediculose; 0+) com sinal de infestação curada; 1) infestação recente, mas baixa probabilidade de parasitismo ativo; 2) com infestação e alta probabilidade de parasitismo; 3) com piolhos móveis (pediculose ativa). RESULTADOS: A prevalência geral foi de 61,4% (79% em meninas e 44% em meninos, p<0,001). Crianças de escolas particulares apresentaram menor prevalência que as de escolas públicas (p=0,02), especialmente devido à baixa prevalência em meninos. Metade das crianças foram classificadas nas classes 0 e 0+; 22% na classe 1; e 28% nos graus 2 e 3. A proporção de crianças no grau 3 foi maior em escolas públicas que particulares. Observou-se diferença significante na intensidade do parasitismo em relação ao sexo, onde para os graus 2 e 3 de parasitismo os valores para meninas excederam em duas vezes àqueles dos meninos. CONCLUSÕES: Sexo e classe social são importantes fatores para a prevalência geral e grau de infestação por P. capitis. A classificação das crianças por intensidade de infestação permitiu delimitação mais precisa do problema, especialmente importante para vigilância e aplicação de medidas de controle.